2014
DOI: 10.1111/pce.12310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiological responses of trees to waterlogging stress

Abstract: One major effect of global climate change will be altered precipitation patterns in many regions of the world. This will cause a higher probability of long-term waterlogging in winter/spring and flash floods in summer because of extreme rainfall events. Particularly, trees not adapted at their natural site to such waterlogging stress can be impaired. Despite the enormous economic, ecological and social importance of forest ecosystems, the effect of waterlogging on trees is far less understood than the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(189 citation statements)
references
References 131 publications
(419 reference statements)
7
181
0
1
Order By: Relevance
“…7, Tables 1 and 2), perhaps because the higher water content in the shallow soil layers in 2014 increased respiration of roots and microbes compared to 2015, when lower soil moisture in the shallow soil layers due to low precipitation and lack of river flooding would have likely restricted respiratory activity (Flanagan and Johnson, 2005). It is also possible that the over-bank flooding of 2014 stressed plants (Kreuzwieser and Rennenberg, 2014), and respiration increased after the flood waters retreated as physiological processes and growth recovered from the stress. Overall the difference in photosynthetic activity between the two study years was remarkably small (Table 2), given the significant contrast that was observed for precipitation and soil moisture content in 2014 and 2015 (Figs.…”
Section: Ecosystem Co 2 Exchangementioning
confidence: 95%
“…7, Tables 1 and 2), perhaps because the higher water content in the shallow soil layers in 2014 increased respiration of roots and microbes compared to 2015, when lower soil moisture in the shallow soil layers due to low precipitation and lack of river flooding would have likely restricted respiratory activity (Flanagan and Johnson, 2005). It is also possible that the over-bank flooding of 2014 stressed plants (Kreuzwieser and Rennenberg, 2014), and respiration increased after the flood waters retreated as physiological processes and growth recovered from the stress. Overall the difference in photosynthetic activity between the two study years was remarkably small (Table 2), given the significant contrast that was observed for precipitation and soil moisture content in 2014 and 2015 (Figs.…”
Section: Ecosystem Co 2 Exchangementioning
confidence: 95%
“…Acetaldehyde is formed from the oxidation of ethanol, and is emitted along the stems and from the leaves (Kreuzwieser et al 1999). Plants transport a great number of organic and inorganic compounds in the xylem sap from roots to the shoot (in poplar: Siebrecht and Tischner 1999;Millard et al 2006;Kreuzwieser and Rennenberg 2014). Besides nitrate (Black et al 2002), also the direct NO precursor nitrite can be transported with the transpiration stream either as anion (Brunswick and Cresswell 1988;Morard et al 2004) or as nitrous acid (HNO 2 , pKa = 3.29) (Shingles et al 1996).…”
Section: No Emission From Aboveground Plant Partsmentioning
confidence: 98%
“…Nitrite is most likely derived from nitrate by the action of NR. Because primary and secondary metabolism in roots of poplar is affected by oxygen deficiency (Kreuzwieser et al 2009;Kreuzwieser and Rennenberg 2014), the cellular pH decreases and NiR is, therefore, inactivated. Since NR activity is still high under these conditions, an accumulation of nitrite occurs (Botrel et al 1996).…”
Section: Belowground No Formationmentioning
confidence: 99%
“…towards effects of water stress depend on several factors, such as imposed types of stress (drought or flooding), their time of duration and especially on the level of tolerance of the genotype, which was notably discrepant, especially when comparing different species (peach tree and plum tree). It is known and reported by several authors in the literature, that water stress provides strong impacts to plants' metabolism, the reduction in photosynthetic capacity and stomatal conductance being considered limiting and triggering several other harmful processes (FERNER et al, 2012;PIMENTEL et al, 2014;KREUZWIESER and RENNENBERG, 2014). According to Kreuzwieser and Rennerberg (2014) there are strong indications that limitations on both stomatal and non-stomatal are involved in the progressive reduction of photosynthetic capacity in plants subjected to environmental stresses.…”
Section: Resultsmentioning
confidence: 99%